Electroanalytical Behavior of Poly-L-Lysine Dendrigrafts at the Interface between Two Immiscible Electrolyte Solutions - Herzog, G.; Flynn, S.; Johnson, C.; Arrigan, Damien (American Chemical Society, 2012)
In this work, the electrochemical behavior of nonredox-active poly-L-lysine dendrigraft molecules of four different generations was investigated at the interface between two immiscible electrolyte solutions (ITIES). The influence of the dendrigraft generation on the electrochemical response, sensitivity of the calibration curves, and limit of detection was studied. Cyclic voltammetry at the ITIES revealed that the sensitivity increased (1840 to 25 800 nA µM-1) and the limit of detection decreased (11.10 to 0.65 µM) as the dendrigraft generation increased from generation G2 through to generation G5, respectively. The results are compared to those for protein voltammetry at the ITIES. Our studies suggest that the sensitivity expected for a synthetic ionized macromolecule can be predicted on the basis of its net charge and its diffusion coefficient. However, electrochemistry at the ITIES demonstrates a greater sensitivity toward proteins, which is attributed to their tertiary structure.